Rekrutmen Program Pemagangan ke Jepang: Suatu Tinjauan Program Pemerintah Daerah - Solechan Solechan (Administrative Law and Governance Journal, 2018)
Apprenticeships can be carried out inside or outside the territory of Indonesia. In Indonesia there are several apprenticeship programs abroad. Apprenticeship abroad is regulated more specifically in the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number PER. 08 / MEN / V / 2008 concerning Procedures for Licensing and Implementation of Overseas Internships. This study aims to know the recruitment of apprenticeship programs to Japan: a review of government programs. This research is normative legal research. The results of the study found that apprenticeship abroad has been regulated more specifically in the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number PER. 08 / MEN / V / 2008 concerning Procedures for Licensing and Implementation of Overseas Internships. The regulation is a mandate and guidance on apprenticeship activities abroad.Keywords: Internship, Japan, Government, Employment AbstrakPemagangan dapat dilaksanakan di dalam maupun di luar wilayah Indonesia. Di Indonesia ada beberapa program pemagangan di luar negeri. Pemagangan di luar negeri diatur lebih spesifik dalam Peraturan Menteri Tenaga Kerja dan Transmigrasi Republik Indonesia Nomor PER. 08/MEN/V/2008 tentang Tata Cara Perizinan dan Penyelenggaraan Pemagangan di Luar Negeri. Penelitian ini bertujuan untuk mengatahui rekrutmen program pemagangan ke Jepang: suatu tinjauan program pemerintah. Penelitian ini merupakan penelitian hukum normatif. Hasil penelitian ditemukan bahwa Pemagangan di luar negeri telah diatur lebih spesifik dalam Peraturan Menteri Tenaga Kerja dan Transmigrasi Republik Indonesia Nomor PER. 08/MEN/V/2008 tentang Tata Cara Perizinan dan Penyelenggaraan Pemagangan di Luar Negeri. Peraturan tersebut sebagai mandat dan panduan kegiatan pemagangan diluar negeri.Kata Kunci: Magang, Jepang, Pemerintah, Ketenagakerjaan